Caracterizacion de aislamientos de Beauveria baáiana para el control de la broca del cafe - Velez Arango, P.E.=700 1 Estrada Valencia, M.N.; Gonzalez Garcia, M.T.; Valderrama Fonseca, A.M.; Bustillo Pardey, A.E.
(Es, En)
Ilus., 25 ref.
Keywords: BEAUVERIA BAáIANA; HYPOTHENEMUS HAMPEI; CONTROL BIOLOGICO; AISLAMIENTO; COSTA RICA